Advancing research on ecosystem service bundles for comparative assessments and synthesis. Issue 1 (31st December 2022) - Meacham, Megan; Norström, Albert V.; Peterson, Garry D.; Andersson, Erik; Bennett, Elena M.; Biggs, Reinette (Oonsie); Crouzat, Emilie; Cord, Anna F.; Enfors, Elin; Felipe-Lucia, María R.; Fischer, Joern; Hamann, Maike; et al.
ABSTRACT: Social-ecological interactions have been shown to generate interrelated and reoccurring sets of ecosystem services, also known as ecosystem service bundles. Given the potential utility of the bundles concept, along with the recent surge in interest it is timely to reflect on the concept, its current use and potential for the future. Based on our ecosystem service bundle experience, expertise, and ecosystem service bundle analyses, we have found critical elements for advancing the utility of ecosystem service bundle concept and deepening its impact in the future. In this paper we 1) examine the different conceptualizations of the ecosystem service bundle concept; 2) show the range of benefits of using a bundles approach; 3) explore key issues for improving research on ecosystem service bundles, including indicators, scale, and drivers and relationships between ecosystem services; and 4) outline priorities for the future by facilitating comparisons of ecosystem service bundle research.